Computational Thinking Initiation. An experience with robots in Primary Education - José Miguel Merino-Armero; José Antonio González-Calero; Ramón Cózar-Gutiérrez; Rafael Villena-Taranilla (Journal of Research in Science, Mathematics and Technology Education, 2018)
Computational Thinking (CT) is an increasingly interesting educational trend, since it is currently thought that the next generation will need to master this skill in order to succeed in modern life. At the same time, research indicates that motivation is a key element that affects the effectiveness of educational processes. Consequently, educators should take into account this fact when designing teaching sequences. In this paper, we present a robotics-based instruction for third-grade students aimed at introducing computational thinking ideas. The experience was carried out with 63 students. An assessment of different indicators concerning learning outcomes, such as mental rotation or computation thinking gains, was performed. In particular, from a motivational perspective, a test developed by Keller (1983; 1987; 2010) was employed in order to assess four dimensions: attention, relevance, confidence and satisfaction. Results show the participants’ high motivation after working with robot computational ideas. These results may eventually support the use of educational robotics in order to promote students’ development of computational thinking in primary schools